Балто-армяно-славянские и балто-арменские параллели в лексико-семантичской группе «части тела и их функции» - Сараджева, Людвига Алексеевна (Baltistica, 1987)
The Baltic–Armenian–Slavic and the Baltic–Armenian parallels in “parts of the body and their functions” The lexico-semantic group considered in this paper reveals some interesting facts about areal interrelations. The Armenian having the nearest kinship to Greek reveals ad hoc closer connections with the Baltic and Slavic. The existence of exclusive isoglosses as well as the group isoglosses not shared by Slavic shows that the contacts between proto-Armenians and proto-Balts were realized not only through the Slavic linguistic area as is adopted by many scholars, but through immediate contacts too. It must also be noted that the Armenian-Baltic isogloss group exceeds the Armenian-Slavic one quantitavely.